Access and efficacy of university mental health services during the COVID-19 pandemic - Wagner, Beverly; Snoubar, Yaser; Mahdi, Yousif S. (Frontiers in Public Health, 2023)
Objective: This study sought to understand the mental health issues, mental health support and efficacy of that support among university students Participants: All students enrolled in a College of Arts and Sciences at one mid-size university received an email that contained a link to an anonymous, online questionnaire developed and disseminated through PsychData. 162 students completed the questionnaire. Methods: Mixed methods: Data was summarized using descriptive analysis, testing for significance, testing for differences, and content analysis.Results: Participants reported high levels of anxiety (76%) and depression (65%). Results indicated that participant demographics were associated with types of mental access, and support. Unexpected results included lack of knowledge or information on cost, and how to access mental health services hindered access for participants, and although telehealth was the most widely used support, in contrast to other studies, participants indicated a preference for face-to-face mental health services. Conclusion: Results highlight the need for improving communication about and access to mental health services in higher education Recommendations and implications for policy and support services are provided.